Use of the Letter of Jude by the Second Letter of Peter - Callan, Terrance (Biblica, 2004)
Assuming that 2 Pet 2,1–3,3 is dependent on Jude 4-18, this essay describes in detail the way the author of 2 Peter has used Jude’s material. It is clear that the author of 2 Peter has not simply incorporated Jude, as is sometimes asserted. Rather, 2 Peter has thoroughly reworked Jude to serve its own purposes. 2 Pet 2,1–3,3 is best described as a free paraphrase of Jude 4-18. The relationship between the two texts is similar to the relationship between 1 Clem 36.2-5 and Heb 1,3-13.